Phosphodiesterase-5 inhibitor sildenafil attenuates kidney injury induced by Bothrops alternatus snake venom - Jorge, Antônio Rafael Coelho; Marinho, Aline Diogo; Silveira, João Alison de Moraes; Nogueira Junior, Francisco Assis; de Aquino, Pedro Everson Alexandre; Alves, Ana Paula Negreiros Nunes; Jorge, Roberta Jeane Bezerra; Ferreira Junior, Rui Seabra [UNESP]; Monteiro, Helena Serra Azul (Elsevier, 2021)
Acute kidney injury pathogenesis in envenoming by snakes is multifactorial and involves immunologic reactions, hemodynamic disturbances, and direct nephrotoxicity. Sildenafil (SFC), a phosphodiesterase 5 inhibitor, has been reported to protect against pathological kidney changes. Objective: This study aimed to investigate the protective effect of sildenafil against Bothrops alternatus snake venom (BaV)-induced nephrotoxicity. Methods: Kidneys from Wistar rats (n = 6, weighing 260–300 g) were isolated and divided into four groups: (1) perfused with a modified Krebs-Henseleit solution (MKHS) containing 6 g% of bovine serum albumin; (2) administered 3 μg/mL SFC; (3) perfused with 3 μg/mL BaV; and (4) administered SFC + BaV, both at 3 μg/mL. Subsequently, the perfusion pressure (PP), renal vascular resistance (RVR), urinary flow (UF), glomerular filtration rate (GFR), and percentage of electrolyte tubular sodium and chloride transport (%TNa+, %TCl−, respectively) were evaluated. The cyclic guanosine monophosphate (cGMP) levels were analyzed in the perfusate, and the kidneys were removed to perform oxidative stress and histopathological analyses. Results: All renal parameters evaluated were reduced with BaV. In the SFC + BaV group, SFC restored PP to normal values and promoted a significant increase in %TNa+ and %TCl−. cGMP levels were increased in the SFC + BaV group. The oxidative stress biomarkers, malondialdehyde (MDA) and glutathione (GSH), were reduced by BaV. In the SFC + BaV group, a decrease in MDA without an increase in GSH was observed. These findings were confirmed by histological analysis, which showed improvement mainly in tubulis. Conclusion: Our data suggest the involvement of phosphodiesterase-5 and cGMP in BaV-induced nephrotoxicity since its effects were attenuated by the administration of SFC.
Keywords: Acute kidney injury; Kidney perfusion; Sildenafil; Snake venom